Intravenous Iron Therapy in Severe Anemia at 28-34 Weeks of Gestation and it’s Feto-Maternal Outcome- A Prospective Study from A Developing Country - Sharma, Sangeeta; Sharma, Naresh (International Journal of Medical Science And Diagnosis Research, 2023)
Introduction: Iron deficiency anaemia (IDA) is the most common nutritional deficiency in pregnancy. Anemia results in poor pregnancy outcome and also affects fetal outcome. This study was undertaken to evaluate the response of intravenous iron given to pregnant women with severe IDA and their feto-maternal outcome. Methodology: A prospective study was conducted in the department of Obstetrics & Gynaecology, at a tertiary care centre of Northern India. Fifty-two pregnant women with haemoglobin between 5-7 g% with diagnosed iron deficiency attending antenatal clinic were given intravenous iron complex Follow-up after 4 weeks was done and IDA specific blood profile was done at baseline and at follow-up. Feto-maternal outcomes were seen at delivery. Results: The mean age of study population was 25.5 ± 3.96 yrs. Improvement at 4 week follow-up from baseline in hemoglobin (p value-0.001) and iron profiles (S. Iron, Total Iron Binding Capacity (TIBC), S. Ferritin) (p value -0.0001) were highly significant. On comparing the Hb levels at delivery after intravenous infusion at 28-34 weeks gestation, 17 patients were still below 8 gm%, whereas 35 were above 8 gm%. Distribution of IUGR, preterm labor and blood transfusion in postpartum period were statistically significant amongst both group (p value<0.05). Fetal outcomes were also evaluated amongst the 2 groups. Distribution of Preterm birth, birth weight and NICU admission was also statistically significant (p value<0.05). Conclusion: The intravascular iron therapy definitely has a rapid increase in haemoglobin which can prevent the complications due to severe anaemia in pregnancy and blood transfusion can also be prevented, but iron stores are not replenished to the optimum level, so there is a need to give replacement therapy (by oral route) post transfusion for long term benefits. The rise of hemoglobin affects feto-maternal outcomes even in the last trimester.contrast agents. This is a first case report of AHCM portrayed by this ingenious technology. Keywords: AMCH, IUGR, TIBC